The Impact of Crude Oil Price Shock: Evidence from Bangladesh - Shen, Qian; Khandoker, Mohammad Sogir Hossain; Saha, Joti; Bhuyan, Rafiqul (International Journal of Economics and Financial Issues, 2024)
This study aims to estimate the impact of crude oil price on the DSEX broad index of the Dhaka stock exchange using the Vector Error Correction Model (VECM) for the study period 2013:01-2022:12. It has decomposed the oil price shock into supply side and demand side oil shock. The empirical result shows that the stock price decreases significantly with crude oil prices driven by the shock in oil production. In contrast, the improvement in global economic activity results in a shock in the oil price which has a significant positive impact on the stock price. Furthermore, the accumulated shock in oil prices has a significant positive impact on stock prices. The variance decomposition under the VEC model shows that the demand shock of oil price contributes more to the variation in stock price for the oil-importing country Bangladesh. Since different oil price shocks have different impacts, the policy maker and investors implement decisions based on the understating of the sources of the shocks.